Seasonal source shifts and toxicity implications of PM2.5-bound polycyclic aromatic hydrocarbons in central China: The critical role of underrated local emissions - Runqi Zhang; Sheng Li; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Pollution Research, 2026)

Field observations reveal biomass burning and cooking as the significant sources of PM2.5-bound organic acids in Central China - Ziyue Xiang; Runqi Zhang; Sheng Li; Bin Xu; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Environment, 2026)

Impact of Open Crop Straw Biomass Burning Emissions on the Air Pollution in the Hunan Province, China: A Case Study - Datong Luo; Lin Luo; Na Wang; Jianxun Wu; Lang Liu (Aerosol Science and Engineering, 2025)
Emissions from open crop straw burning (OCSB) during crop harvest have exerted considerable impacts on the air quality in China, but the quantitative evaluation of OCSB to air pollutants remains insufficient. In the study, the WRF-Chem model is used to quantitatively evaluate the impacts of OCSB on the air quality in Hunan, China from October 15 to 26, 2024. During the study episode, OCSB contributes 45.7% and 16.8% of the anthropogenic emission of organic carbon and non-methane volatile organic compounds, respectively. Model simulations show that OCSB emissions account for 2.8% of the maximum daily 8-hour average ozone (MDA8 O 3 ) concentration, but play a more substantial role in particulate pollution, contributing 25.6% to near-surface fine particulate matter levels. OCSB is an important organic aerosol (OA) source, increasing primary OA by 46.2% and secondary OA by 62.7%. The enhanced OA accounts for 54.8% of the total PM 2.5 increase induced by OCSB emissions. Sensitivity experiments show that the concentrations of aerosol species generally decrease linearly with reduced OCSB emissions, while MDA8 O 3 concentrations exhibit a non-linear trend due to the complex responses to its precursors. Implementing the clean disposal of straw residue during crop harvest presents an effective strategy to improve the air quality in Hunan.

Intermediate-volatility aromatic hydrocarbons from the rubber products industry in China - Zhou Zhang; Yanli Zhang; Lilin Zou; Zhongxiangyu Ou; Datong Luo; Zhan Liu; Zhonghui Huang; Leilei Fei; Xinming Wang (Science of The Total Environment, 2023)

Compensatory thalamocortical functional hyperconnectivity in type 2 Diabetes Mellitus - Jie Wang; Shanlei Zhou; Datong Deng; Mimi Chen; Huanhuan Cai; Cun Zhang; Fujun Liu; Wei Luo; Jiajia Zhu; Yongqiang Yu (Brain Imaging and Behavior, 2022)

Downregulation of galectin-3 by EGF mediates the apoptosis of HepG2 cells - Zhenzhen Hu; Xiuqin Jiang; Ying Xu; Nan Lu; Weizhi Wang; Jie Luo; Han Zou; Datong Zheng; Xing Feng (Molecular and Cellular Biochemistry, 2012)